2017
DOI: 10.7448/ias.20.1.21416
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of sexual orientation to health professionals in China: results from an online cross‐sectional study

Abstract: Background: Many men who have sex with men (MSM) in China are “in the closet.” The low rate of disclosure may impact sexual behaviours, testing for HIV and other sexually transmitted infections (STIs), and diseases transmission. This study examines factors associated with overall sexual orientation disclosure and disclosure to healthcare professionals. Methods: A nationwide cross-sectional online survey was conducted from September 2014 to October 2014 in China. Participants completed questions covering socio-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 31 publications
1
61
1
Order By: Relevance
“…This finding is consistent with other non-network based survey studies in China [15] and in the US [50]. Disclosure to healthcare professionals is important for provider-driven HIV testing [14,50,51].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with other non-network based survey studies in China [15] and in the US [50]. Disclosure to healthcare professionals is important for provider-driven HIV testing [14,50,51].…”
Section: Discussionsupporting
confidence: 90%
“…These disclosure targets can offer MSM support, provide access to information, and potentially facilitate HIV testing [13,14]. Disclosing to others, especially to health professionals, is positively correlated with HIV testing across different settings [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with sexual or gender minority identities or behaviors may face disclosure barriers due to internalized homophobia or transphobia, concern of stigma or discrimination, legal impacts, and lack of comfort with the provider. [27][28][29][30][31] Reback and Larkins 23 found that heterosexually identified men who have sex with men engaged in distancing strategies because they saw their behaviors as incongruent with their identity, which brought up feelings of shame and disgust for many of them. Lack of disclosure to healthcare providers has been found to decrease recommendations for appropriate health services, including HIV testing services.…”
Section: Discussionmentioning
confidence: 99%
“…Before 2008, the main settings where Chinese MSM identi ed male partners were public parks, bars, or bathhouse. (26) Considering that many Chinese MSM reported discomfort with visiting gay bars or bathhouses due to fears of being identi ed in public as a gay man, (27) challenges identifying potential male partners may have delayed their age at sexual debut. However, the rise in popularity of the internet and social media (i.e., gay dating apps) sites for MSM in China has reduced challenges associated with sexual partner seeking, potentially facilitating sex initiation at earlier ages.…”
Section: Discussionmentioning
confidence: 99%